Po Trakų Dievo Motinos karūna = Under the crown of Our Lady of Trakai - Paknys, Mindaugas 1973- (Vilniaus dailės akademijos leidykla, 2018)
This publication has been intended not only to publish the research on the painting of Our Lady of Trakai, but also to give publicity to various phenomena related to the painting and its historical impact. As was mentioned, the entire religious life of Trakai revolved around the painting of Our Lady of Trakai, and thus various episodes of this life are revealed.
Keywords: Gottesmutter von Trakai; Geschichte 1400-1700; Ikone; Mariendarstellung; Wallfahrt; Vytautaskirche -- Trakai; Aufsatzsammlung